(untitled) (Research, Society and Development, 2022)
Virgin olive oil is the product obtained only from the fruit of the olive tree, where it cannot contain any type of oil or mixture of oils in any proportion. The objective of the present study was to evaluate the labeling and visual integrity on virgin olive oil packages sold in the city of Dourados (MS, Brazil). Two markets that sell the most different brands of olive oil were selected, and five brands of virgin olive oil were analyzed. The marks were coded as A, B, C, D and E. Data collection was performed through photographic records, whose monitoring was carried out every 15 days for a period of thirty days. Data analyzes were performed using a checklist to verify and compare “compliance” and “non-compliance” with the Legislation. According to the results found, brands B and E presented their labels in accordance with Brazilian legislation. Brands A, C and D were not in accordance with the Legislation referring to Normative Instruction No. 1/2012; RDC No. 259 ANVISA; Regulation n°1019/2002 on the marketing standards for olive oil; RDC No. 359 of ANVISA; In RDC No. 360 and Law No. 10,674. Therefore, it can be concluded that it is essential that regulatory and supervisory bodies are pending both products and labels so that industrial companies can follow the regulations and market food safely.